Mock Me! A Guide to Developing a First rate Training tool on a Second rate Budget - Galen Baxter (Georgia Southern University, 2017)
Background: Working closely with county Environmental Health Specialists through the Standardization Process, a critical need was identified. Assistance was needed in prioritizing inspections based on risk levels identified in restaurant kitchens during inspections. Additionally, more training was needed to help them identify other areas in food service establishments that require further assessment. Methods: Tight budget constraints prevented the purchase of expensive training equipment; however, with a little creativity and team work, a mock kitchen made entirely out of cardboard, tape and a couple of aluminum pans was created as a portable, handson training tool that could be easily transported around the state. Results: Overwhelming positive feedback was received from the districts that experienced training using the tool. Environmental Health Specialists suddenly had an opportunity to practice and apply what they had learned within a controlled environment and increase their confidence in assessing and prioritizing during inspections. Conclusions: Solutions to problems can sometimes be found using a very simple approach. A little bit of creativity and a willingness to literally "think outside the box" can go a long way in providing viable, alternative solutions to common roadblocks in government. The key to creating an effective training tool is to accurately identify training gaps in the intended audience. Key words: hands-on; training; creativity; budget